H2-rich Syngas Production in Catalytic Steam Gasification of Palm Kernel Shell Using Coal Bottom Ash - SHAHBAZ, MUHAMMAD (2018)
The production of syngas through biomass gasification is a promising and environmentally friendly technique to fulfill the growing energy demand. However, the quality and quantity of syngas produced significantly depend on the type of biomass, gas cleaning process, removal of by-products, and gasification technique.